QUATERNARY SOIL-GEOLOGICAL STRATIGRAPHY IN GREECE - Paepe, R.; Mariolakos, I.; Van Overloop, E.; Nassopoulou, S.; Hus, J.; Hatziotou, M.; Markopoulos, T.; Manutsoglu, E.; Livaditis, G.; Sabot, V. (Bulletin of the Geological Society of Greece, 2018)
Peloponnesus and Crete are probably offering the best possible standard sections for Eastern Mediterranean Pleistocene Series. Complete Pleistocene Standard Lithostratigraphic Sections from Sparta (Peloponnesus) and Kandanos (Crete) reveal continuous Pleistocene Land Sequences composed of cyclic palaeosol levels interfering with clastic fluvial, eolian (loess) and gravel deposits comparable with analogues found elswhere over the earth. Most suitable for correlation are: a) the standard Idfess area of Northern Europe, Russia and China, and b) the subtropical and tropical regions of Africa and Asia. The standard Greek Pleistocene Lithostratigraphic Sequence independently recorded at both sites (and partially from sites in other regions of Greece) reveal a number of 103 palaeosols of both interglacial and interstadial stages, indicating the extreme warm to relative warm phases of the Pleistocene ice age. This number suits surprisingly well to the 103 levels of the equally warm odd numbered oxygen isotopie stages (OIS) of the Pleistocene deep sea record which equally encompass the warm phases of the Pleistocene. Special attention is given to the Upper Pleistocene of Koroni (Southern Peloponnesus) as a case study for the Last Interglacial - Last Glacial Cycle, i.e. the middle term cycle extending in time from 127 Ka (thousand years) till 10 Ka or beginning of the Holocene. It stands as a model for the recurrent 100 Ka cycles of the long term overall Pleistocene record. Finally, in addition to the Pleistocene, the twenty wet - dry cycles of the Holocene are reviewed.